ANALISIS PENGUJIAN PECKING ORDER THEORY DAN TRADE OFF THEORY TERHADAP STRUKTUR MODAL (Studi kasus pada Perusahaan Manufaktur Sub Sektor Kimia Di Bursa Efek Indonesia) Tahun 2012-2016) - Pratiwi, Hanni; Panjaitan, Fery; Ahmad Agin, Arka’a (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
The purpose of this research is to analyze and test the pecking order theory and trade-off on the capital structure at a manufacturing company of the chemical sub-sector listed in Bursa Efek Indonesia. The sampling method used is purposive sampling. The data collection method used is the data analysis method. The data used are in the form of financial statements of manufacturing companies that have been audited from 2012-2016. This research uses multiple regression analysis methods. As a tool in the processing of statistical data uses SPSS 22 program. The result of this research shows that asset structure, capital intensity, liquidity, profitability, and company growth have no significant effect on the capital structure while the firm size and stock price have a significant effect on capital structure. The structure of the asset has no significant effect (109,875) with a significant level (0,224) to capital structure, firm size influential significantly with value (-11,931) with a significant level (0.021) to capital structure, capital intensity does not significantly influence value (- 26,059) with significant level (0.303) on capital structure, liquidity does not significantly influence value (0,474) with significant level (0.891) to capital structure, profitability has no significant effect (-219.342) with significant level (0.281) to capital structure, The share price significantly influences the value (0.401) with the significant level (0.31) to the capital structure, the company’s growth does not significantly influence the value (213,510) with the significant level (0.141) And the asset structure, firm size, capital intensity, liquidity, profitability, stock quotes and growth of the company have a significant effect to the capital structure simultaneously. Based on the calculation Fcount is 9,636 greater than Ftabel 2,61 with a significant level of 0,000. The value of the coefficient of determination in the regression model is 0.799 this value indicates that the variable ability of asset structure, firm size, capital intensity, liquidity, profitability, stock price, and company growth in explaining the variable of capital structure is equal to 79.9% while the rest is equal to 20.1 % which is explained by other variables not included in the regression model in this study.